Optimization Of Multigravity Separation For Recovery Of Ultrafine Coal - M. Menéndez (Society for Mining, Metallurgy & Exploration, 2007)
Enhanced gravity separation appears to be one of the most promising methods for processing all types of <200-µm coal feeds and tailings. Systems based on this technology are reviewed, and the results of investigations based on C900 Multi-Gravity Separator tests conducted to assess the treatment of <200-µm, extremely difficult-to-wash coal settling pond tailings are presented. Multi-Gravity Separator processing tests of ultra-fine tailings with a high clay particle size content (22.6% <10 µm and 60.1% <40 µm) and a 69.56% ash content show that this material can be effectively treated after desliming (<10 µm) of clay-size particles to produce a coal with a 20.6% ash at a separator combustible material recovery of 69.3%. Desliming is shown to be critical in reducing coal ash content and combustible material recovery. Similar improvements are anticipated in the recovery and separation pro-cesses for other enhanced gravity separation systems from the desliming of feeds. Although not a conventional form of treating Multi-Gravity Separator data, the existence of well-defined polynomial relationships based on the product of drum shake amplitude and shake frequency relative to product coal recovery, product ash content and yields at varying wash water flows is demonstrated. Low-amplitude and intermediate- to high-frequency bed agitation are shown to produce optimum ash reduction results.